Preliminary Design Analysis of a New Field Excitation Flux Switching Machine with Segmental Rotor and Non-overlap Winding - F. Omar, M; Sulaiman, E; A. Soomro, H; M. Romalan, G; M. N. S. Othaman, S (International Journal of Engineering and Technology, 2018)
Recently, a three-phase Field Excitation Flux Switching Motor (FEFSM) with salient rotor structure has been introduced with their advantages of easy rotor temperature elimination and controllable FEC magnetic flux particularly meet for high torque, high power as well as high speed diverse performances. Nevertheless, the salient rotor structure is found to lead a longer magnetic flux path between stator and rotor producing weak flux linkage along with low torque performances. Therefore, a new structure of a single-phase FEFSM using segmental rotor with non-overlap windings is proposed. Segmental rotor and non-overlap windings are the clear advantages of these topologies as the copper losses gets reduce and rotor becomes less weight as well as more robust. Detailed analysis on winding arrangement test analysis, armature and FEC flux linkage, back-EMF and average torque characteristics have been performed by using 2D Finite Element Analysis (FEA) through JMAG version 15 software. The results show that the proposed motor with segmental rotor and non-overlap windings produce short flux path, high flux linkage and the highest torque capability achieved is 0.91 Nm.Â Â